Areas of application of knowledge: foundations and initiatives for different languages - Krachunov, Krasnomir (Yearbook Telecommunications, 2018)
1. Knowledge is used and built in four main areas defined by the following opposites: material-ideal, perceptions-concepts. For the proper use of knowledge, different rules or logic are built. 2. An analysis of the starting point of logics has been made and links have been sought with some general headings in each particular area. 3. A common position is selected from each area and links to the logic beginnings are listed.